Electronic Security and Sharia Compliance: Addressing Legal Challenges In Digital Banking In Indonesia - Rifazul Adzmi; Edo Segara Gustanto; Rusdi Rizki Lubis; Setiyawan Gunardi (Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
Non-Indexed Publication